Isolation and identification of plant growth‐promoting rhizobacteria from tall fescue rhizosphere and their functions under salt stress. Issue 6 (17th November 2022) - Li, Youyue; You, Xiangkai; Tang, Zhe; Zhu, Tianqi; Liu, Bowen; Chen, Mo‐Xian; Xu, Yuefei; Liu, Tie‐Yuan
Abstract: Soil salinity has become one of the major factors that threaten tall fescue growth and turf quality. Plants recruit diverse microorganisms in the rhizosphere to cope with salinity stress. In this study, 15 plant growth‐promoting rhizobacteria (PGPR) were isolated from the salt‐treated rhizosphere of tall fescue and were annotated to 10 genera, including Agrobacterium, Fictibacillus, Rhizobium, Bhargavaea, Microbacterium, Paenarthrobacter, Pseudarthrobacter, Bacillus, Halomonas, and Paracoccus . All strains could produce indole‐3‐acetic acid (IAA). Additionally, eight strains exhibited the ability to solubilize phosphate and potassium. Most strains could grow on the medium containing 600 mM NaCl, such as Bacillus zanthoxyli and Bacillus altitudinis . Furthermore, Bacillus zanthoxyli and Bacillus altitudinis were inoculated with tall fescue seeds and seedlings to determine their growth‐promoting effect. The results showed that Bacillus altitudinis and mixed culture significantly increased the germination rate of tall fescue seeds. Bacillus zanthoxyli can significantly increase the tillers number and leaf width of seedlings under salt conditions. Through the synergistic effect of FaSOS1, FaHKT1, and FaHAK1 genes, Bacillus zanthoxyli helps to expel the excess Na + from aboveground parts and absorb more K + in roots to maintain ion homeostasis in tall fescue. Unexpectedly, we found that Bacillus altitudinis displayed an inapparent growth‐promoting effect on seedlings under salt stress. Interestingly, the mixed culture of the two strains was also able to alleviate, to some extent, the effects of salt stress on tall fescue. This study provides a preliminary understanding of tall fescue rhizobacteria and highlights the role of Bacillus zanthoxyli in tall fescue growth and salt tolerance.